Financial Control and its’ impact on Organizational performance – An empirical study of J/Municipal Council - Yogendrarajah, R. (International Conference on Competency Building Strategies in Business & Technology at SaiRam Institute, India. – 2011., 2011)
In the modern management, financial control is very important. If the financial control is effective, the organization will grow effective in future. Financial control is one of the performance control tool that are used by managers. Today many Public organizations provide services to the public. Jaffna municipal council is a public organization that deals with people of Jaffna city to fulfill their daily needs. The Jaffna municipal council provides different services to the public and it faces many difficulties to manage these activities. However it serves with the help of government grants and other funds from various non government organizations it faces some problems regarding finance and other physical resources. The purpose of this study is to analyze how the financial control of the Jaffna municipal Council affects its organizational performance. For this purpose two hypothesis were tested. One is “Effective budgetary control has positive impact on its organizational performance” and other is “Effective financial control leads to better organizational performance”. To test this hypothesis the data were obtained through primary data such as interview, interrogation and discussions with financial officers and from annual reports and statements as secondary data. Financial information is analyzed by using various analysis methods. Ratio analysis, percentage analysis and gap analysis are used to measure effectiveness of financial control. Organizational performance is measured by budgetary control with the significance of variance. In this research, when the budgetary control is ineffective the organizational performance based on budgetary control is worst. And the effective financial control leads to better organizational performance. Finally, this research has proved that there is positive relationship between financial control and organizational performance and there is positive control and relationship between budgetary control and organizational performance. So, It can be concluded the public organization should take attention in the financial control to manage the activities effectively.
Keywords: Financial control; Organizational performance; Budgetary control